2007
DOI: 10.1007/978-0-387-72486-7_2
|View full text |Cite
|
Sign up to set email alerts
|

Open Source Collaboration for Fostering Off-The-Shelf Components Selection

Abstract: Abstract. The use of Off-The-Shelf software components in ComponentBased Development implies many challenges. One of them is the lack of available and well-suited data to support selection of suitable OTS components. This paper proposes a feasible and incremental way to federate and reuse the different efforts for finding, selecting, and maintaining OTS components in a structured way. This is done not only for supporting OTS components selection, but also to overcome reported problems with the integration and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 17 publications
(28 reference statements)
0
16
0
Order By: Relevance
“…4 (119) exceeds the number of OSS projects that have SA documentation (108), because one OSS project may employ several formats (e.g., both Html and picture) to document SA. Design information contained in OSS projects, e.g., architectural information, is often not detailed enough, and usually unstructured, presented in many different forms (e.g., web pages, forums, files, mailing lists) [9]. As presented in Section III.C, in this survey, we focus on the architectural information archived within the OSS repositories in documents, e.g., files and web pages.…”
Section: B) Project Types and Sadmentioning
confidence: 99%
See 1 more Smart Citation
“…4 (119) exceeds the number of OSS projects that have SA documentation (108), because one OSS project may employ several formats (e.g., both Html and picture) to document SA. Design information contained in OSS projects, e.g., architectural information, is often not detailed enough, and usually unstructured, presented in many different forms (e.g., web pages, forums, files, mailing lists) [9]. As presented in Section III.C, in this survey, we focus on the architectural information archived within the OSS repositories in documents, e.g., files and web pages.…”
Section: B) Project Types and Sadmentioning
confidence: 99%
“…Consequently, the documentation of OSS projects is less emphasized in at least some OSS projects [8]. The information contained in those documents is presented in various forms such as Office files, web pages, and images [9].…”
Section: Introductionmentioning
confidence: 99%
“…Searches in search engines usually yield huge, unwieldy sets of results. A centralized experience portal for sharing OTS componentrelated knowledge between organizations, probably using a global OTS Wiki [15] could be a solution. The results of our industrial surveys have revealed gaps between theory and practice regarding the use of OTS components.…”
Section: Fact 10mentioning
confidence: 99%
“…In addition, the results regarding RQ2 show that knowledge sharing between companies is rare. To facilitate knowledge sharing internally, one possible strategy is to have an internal component 'knowledge keeper' (Li et al 2006 between organizations, probably using a global OSS Wiki (Ayala et al 2007), could be a solution.…”
Section: Recommendation 4: Facilitate the Sharing Of Internal And Extmentioning
confidence: 99%